BALANCED SCORECARD ANALYSIS AS CORPORATE PERFORMANCE MEASUREMENT (Case Study at PT PLN (Persero) Area Malang) - Nugroho, Aditya; di, Rosi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to measure how PT. PLN Area Malang performance using Balanced Scorecard concept. Balanced Scorecard is strategic management system that translate mission and strategy of organisation in objective and operational measurement. Objective and measurement develop to four perspective namely: financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. This case study research use primary data and secondary data from 2012-2013. Data collecting technique conducted using interview with management and employee in charge at PT PLN Area Malang, and also using documentation method, that is data collection which source from report or note in company. Four perspective used in this research consist of financial perspective (ROA, Profit margin, TATO, operating ratio), customer perspective (customer retention, customer acquisition, customer complain) internal business process perspective (SAIDI, SAIFI and connection shrink) and learning and growth perspective (employee productivity,employee training and employee turnover). The results of PT PLN Area Malang performance measurement with Balanced Scorecard approach generally has shown balance performance between every perspective. Customer perspective and learning and growth perspective gain higher performance from year 2012 to year 2013, while financial perspective and internal business perspective experience degradation performance from year 2012 to year 2013. Keyword: Performance Measurement, Balanced Scorecard, PT PLN Area Malang